Pacemaker and ICD oversensing induced by movements near the MRI scanner bore. Issue 12 (23rd November 2016) - Mattei, E.; Censi, F.; Calcagnini, G.; Falsaperla, R.; Genovese, E.; Napolitano, A.; Cannatà, V.
Abstract : Purpose: The effect of the movement near the MRI scanner bore for people with a pacemaker (PM) or an implantable cardioverter defibrillator (ICD) is experimentally evaluated and discussed. Methods: The authors performed in vitro measurements on a saline‐filled human‐shaped phantom (male, 170 cm height), equipped first with an MR‐conditional PM (bicameral configuration, DDD programming), then with an MR‐conditional ICD (biventricular configuration, detection algorithms enable but shock delivery disable). Both the devices were able to transmit in real‐time the detected cardiac activity (electrograms) while moving the phantom around the MRI scanner. The phantom was also equipped with an accelerometer and a magnetic field probe to measure the angular velocity and the magnetic field variation during the experiment. Unipolar versus bipolar sensing mode and maximum sensitivity versus nominal settings were tested. Results: The sensing functions of the PM and ICD systems began to react to motion induced electromagnetic interference starting at an angular velocity as low as 2 rad/s (|d B /dT| = 2 T/s). The motion induced EMI in PM and ICD systems was interpreted as sensed intrinsic heartbeats which resulted in inappropriate pacing inhibition and arrhythmia classification. At the maximum speed of about 6 rad/s (|d B /dT| = 3 T/s), the induced EMI affected classification of ectopic beats and two episodes of VF were inappropriately recorded. Conclusions: These results demonstrate that motion in and around an MR scanner can induce EMI significant enough to be misinterpreted by implanted PMs and ICDs leading to inappropriate changes in therapy. These findings highlight that PM or ICDs, including MR‐conditional systems should not enter the MRI room, except in case of an examination under specified conditions.